Transpterygoid Endoscopic Approach for Inverted Papilloma of the Sphenoid Sinus: A Case Report - Serrano, Candelaria; Redivo, Micaela; Minghera, María del Pilar; Ruggeri, Carlos S. (Revista del Hospital Italiano de Buenos Aires, 2024)
We describe a clinical case of a woman with an inverted papilloma in the sphenoidal sinus.The sphenoid was highly pneumatized, and the inverted papilloma extended into a lateral recess of the sinus beyond the paraclival segment of the internal carotid artery, which was prominent.We performed a unilateral endonasal approach, combining a bilateral sphenoidotomy with a posterior septectomy and a transpterygoid approach to expose the lateral  pneumatized recess of the sphenoid located behind the posterior wall of the maxilla.We resected completely the inverted papilloma with no evidence of recurrence.
Keywords: sphenoidal sinus; inverted papilloma; endoscopic surgery; transpterygoid approach